Materialographic investigations of plate slags from the Late Bronze Age copper production site of Prigglitz-Gasteil (Lower Austria). (April 2023) - Haubner, Roland; Strobl, Susanne; Trebsche, Peter
Highlights: The microstructures of various slags from the Bronze Age mining settlement of Prigglitz-Gasteil are described in detail. A SnO2 particle was found on one slag and small amounts of Sn were detected in 3 of 10 slags. This can be explained by the fact that, in addition to copper smelting, bronze processing was also carried out in Prigglitz-Gasteil. Abstract: This paper presents the microstructures and chemical analyses of 10 plate slags from the Late Bronze Age copper production site of Prigglitz-Gasteil in Lower Austria. The analytical results of overview measurements (XRF) and local measurements on metallographic samples (SEM-EDX) are compared. The samples belong to the category of thin plate slags (PS-C, thickness < 0.5 cm) and the newly defined category of very thin plate slags (PS-D, thickness < 0.2 cm). From their chemical and phase composition, three groups could be distinguished. These different groups did not indicate separate stages during the working process but rather haphazard variations. The amount of residual Cu observed in all the plate slags was small (average Cu content 0.59 wt%), indicating an efficient process of copper smelting, comparable with other prehistoric copper production sites in the Eastern Alps. Remarkably, some of the investigated plate slags contained Sn as a trace element which most likely came into the slag through contamination from the nearby bronze processing. In line with previous archaeometallurgical investigations, the analysis of plate slags confirms that primary and secondary metallurgy were carried out in immediate vicinity at the Prigglitz-Gasteil site.